Effect of Fertilizers and Mycorrhizal Application on Growth and Yield of Shallot - Alfu Laila; Endang Sulistyorini; Weksi Budiaji (SEAS (Sustainable Environment Agricultural Science), 2025)
The study investigated the combined effects of fertilization and arbuscular mycorrhizal fungi (AMF) inoculation on the growth and yield of shallot (Allium cepa var. aggregatum Group) under pot conditions. A randomized complete block design was employed with two factors: fertilizer type (NPK, NK, humic acid, and no treatment) and AMF dose (0, 5, and 10 g plant-1), each replicated three times. Growth traits, including plant height and leaf number, alongside yield components such as bulb number and bulb weight, were measured and statistically analyzed using ANOVA and Duncan's Multiple Range Test. The result showed that fertilization had a significant effect on growth and yield parameters. NPK consistently promoted the greatest plant height and bulb weight, while humic acid alone resulted in lower values, indicating its better suitability as a supplementary amendment rather than a primary nutrient source. AMF inoculation demonstrated potential to increase yield traits, with 10 g per plant dose improving bulb weight and bulb number.